Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1002/rcm.3183
|View full text |Cite
|
Sign up to set email alerts
|

Routine hydrogen isotope measurement of cellulose nitrate by high‐temperature pyrolysis – reference materials and precision

Abstract: The determination of isotope ratios of non-exchangeable hydrogen in tree-ring cellulose is commonly based on the nitration of wood cellulose followed by online high-temperature pyrolysis and isotope ratio mass spectrometry measurement of cellulose nitrate samples. The application of this method requires a proper calibration using appropriate reference materials whose delta(2)H values have been reliably normalized to the V-SMOW/SLAP scale. In our study, we achieve this normalization by a direct alternating meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…In addition, the inter-annual standard deviation is twice as large for one station (8.1 ) compared to the other (4.8 ) over the same period. Knöller et al (2007) observed a difference up to 47.3 between replicates of a standard. They attribute this large variation to evaporative effects during the analysis procedure.…”
Section: Inter-station Variability Of the Hydrogen Isotopic Compositionmentioning
confidence: 92%
See 1 more Smart Citation
“…In addition, the inter-annual standard deviation is twice as large for one station (8.1 ) compared to the other (4.8 ) over the same period. Knöller et al (2007) observed a difference up to 47.3 between replicates of a standard. They attribute this large variation to evaporative effects during the analysis procedure.…”
Section: Inter-station Variability Of the Hydrogen Isotopic Compositionmentioning
confidence: 92%
“…The determination of non-exchangeable δD values in cellulose are based on nitration of wood cellulose (Alexander and Mitchell 1949), followed by online combustion and IRMS measurements of cellulose nitrate samples (Knöller et al 2007). The calibration with respect to the IAEA-VSMOW standard is performed with the two long-term validated versus IAEA-VSMOW and IAEA-SLAP wood cellulose nitrate standards.…”
Section: Tree-ring Datamentioning
confidence: 99%
“…[3][4][5][6] The advent of continuous-flow isotope-ratio mass spectrometry (CF-IRMS) coupled with thermal conversion elemental analyzers (TC/EAs) has enhanced δ 2 H measurements by allowing analysis of smaller sample sizes with faster sample throughput. [15][16][17] Despite these advances, there are shortcomings in the analytical protocols because the same hydrogen isotopic composition may not be obtained in different laboratories for the same homogeneous keratin material.…”
mentioning
confidence: 99%
“…Because atmospheric oxygen is trapped in capsules with water, a correction must be made for its amount and isotopic composition. Knöller et al 10. used a strategy to minimize the effects of evaporation during weighing by weighing water under an argon atmosphere and loading an amount of water about 2 to 10 times larger (2 µL) into capsules.…”
mentioning
confidence: 99%